Pengaruh Optimalisasi Pemanfaatan Media Sosial Instagram dan Brand Awareness terhadap Peningkatan Penjualan Produk pada Usaha Mikro Kecil dan Menengah di Event Saboak Kota Kupang - Sionsy Welda Mariene Sellu; Mas’Amah; Frengky Dupe (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the responses of UMKM at the Saboak Event regarding the use of Instagram social media, brand awareness, and increased sales, analyze the effect of optimizing the use of Instagram social media on increasing sales in UMKM at the Saboak Event, analyze the effect of brand awareness on increasing product sales in UMKM at the Saboak Event, and analyze the effect of simultaneous optimization of the use of Instagram social media and brand awareness on increasing product sales in UMKM at the Saboak Event. This study uses an explanatory method with a quantitative approach through interviews, questionnaires, and documentation studies at the Kupang City Tourism Office as the agency that manages the saboak event. The data were analyzed using multiple linear regression analysis and enriched with the social impact theory framework and social media marketing theory. The results of the study indicate that optimizing Instagram and brand awareness have a positive and significant impact on increasing product sales. Brand awareness has the most dominant influence compared to optimizing social media. This study also provides recommendations for UMKM participating in the Saboak event to optimize their use of Instagram, particularly in terms of frequency and consistency in uploading content.